A review of the state of the science on wearable thermoelectric power generators (TEGs) and their existing challenges. (June 2017) - Siddique, Abu Raihan Mohammad; Mahmud, Shohel; Heyst, Bill Van
Abstract: Thermoelectric generators are solid state energy harvesters which can convert thermal energy into electrical energy in a reliable and renewable manner. Over the last decade, the human body has been considered as a good source of heat to harvest electrical energy through wearable thermoelectric generators. It may become an alternative power generation technique compared to other conventional ones used for many wearable devices. The wearable thermoelectric generator has potential to generate sufficient energy for any wireless sensor nodes (typically power requirements<mW). In this paper, a survey of thermoelectric generators has been comprehensively presented with a specific focus given to the rigid and flexible types of thermoelectric generators. The basic principle of the thermoelectric power generator, applications, and some existing challenges has also been discussed.